Insights into the thermolytic transformation of lignocellulosic biomass waste to redox-active carbocatalyst: Durability of surface active sites - Oh, W.-D. (Elsevier B.V., 2018)
The thermolytic transformation of lignocellulosic spent coffee grounds to superior redox-active carbocatalyst (denoted as NBC) via nitrogen functionalization in a pyrolytic environment at various temperatures was investigated. The intrinsic (e.g. surface chemistry, degree of graphitization, etc.) and extrinsic (e.g. specific surface area, morphology, etc.) properties of the catalysts were systematically studied using various characterization techniques. The three main N configurations conducive to redox reactions, namely pyrrolic N, pyridinic N and graphitic N were present at different compositions in all the NBCs prepared at pyrolysis temperature â¥500 Â°C. The NBCs were used as peroxymonosulfate (PMS) activator for degrading bisphenol A. It was found that NBC-1000 (prepared at 1000 Â°C) has the highest catalytic performance (kapp = 0.072 minâ1) due to the relatively higher specific surface area (438 m2 gâ1), excellent degree of graphitization, and optimum N bonding configuration ratio. Based on the radical scavenger and electron paramagnetic resonance studies, the nonradical pathway involving 1O2 generation is identified as the prevailing pathway while the radical pathway involving SO4radâand radOH generation is the recessive pathway. Further investigation of the durability of surface active sites revealed that the active sites undergo N bonding configuration reconstruction and cannibalistic oxidation (increase in surface oxygen content) during PMS activation reaction. The graphitic N manifest greater catalytic activity and stability compared to pyridinic N and pyrrolic N under oxidizing environment. The results demonstrated that reaction optimization is critical to improve the durability of the catalyst. This study provides useful insights in converting lignocellulosic biomass waste into functional catalytic material, and the strategy to improve the durability of carbocatalysts for redox-based reactions. Â© 2018 Elsevier B.V.